Molecular Characterization of Penicillin-Binding Protein2x, 2b and 1a of Streptococcus pneumoniae Causing Invasive Pneumococcal Diseases in China: A Multicenter Study - Zhou, Menglan; Wang, Lulu; Wang, Ziran; Kudinha, Timothy; Wang, Yao; Xu, Yingchun; Liu, Zhengyin (Frontiers in Microbiology, 2022)
Streptococcus pneumoniae is a common human pathogen that can cause severe invasive pneumococcal diseases (IPDs). Penicillin-binding proteins (PBPs) are the targets for β-lactam antibiotics (BLAs), which are the common empirical drugs for treatment of pneumococcal infection. This study investigated the serotype distribution and antibiotic resistance patterns of S. pneumoniae strains causing IPD in China, including exploring the association between penicillin (PEN) susceptibility and PBPs variations. A total of 300 invasive S. pneumoniae isolates were collected from 27 teaching hospitals in China (2010-2015). Serotypes were determined by Quellung reaction. Serotypes 23F and 19F were the commonest serotypes in isolates from cerebrospinal fluid (CSF), whilst serotypes 19A and 23F were most commonly seen in non-CSF specimens. Among the 300 invasive S. pneumoniae strains, only one strain (serotype 6A, MIC=0.25μg/ml) with PEN MIC value ≤ 0.25μg/ml did not have any substitutions in the PBPs active sites. All the strains with PEN MIC value ≥ 0.5μg/ml had different substitutions within PBPs active sites. Substitutions in PBP2b and PBP2x active sites were common in low-level penicillin-resistant S. pneumoniae (PRSP) strains (MIC=0.5μg/ml), with or without PBP1a substitution, while all strains with PEN MIC ≥ 1μg/ml had substitutions in PBP1a active sites, accompanied by PBP2b and PBP2x active site substitutions. Based on the three PBPs substitution combinations, a high degree of diversity was observed amongst the isolates. This study provides some new insights for understanding the serology and antibiotic resistance dynamics of S. pneumoniae causing IPD in China. However, further genomic studies are needed to facilitate a comprehensive understanding of antibiotic resistance mechanisms of S. pneumoniae.